BIM-TECHNOLOGY METHOD AND MODELS IN THE DESIGN OF THE AQUAPARK DOME STRUCTURE WITH WOODEN ARCHES (Collection of scientific works «Modern structures of metal and wood», 2021)
Тhe  issues  of  designing  a  multi-volume  dome  structure  for  a  water  park  using wooden arches as load-bearing structures are сonsidered. The complexity of the volumes and their joining lines, as well as the requirement to perform non-linear analysis of large-span timber elements at  the  request  of  Eurocode  5,  make  an  information  model  with  elements  of  BIM-technology necessary. It is noted that design using this technology is developing in the direction of taking into account all stages of the structure life cycle. Wood Information modeling is the most prepared for the use of BIM-technologies. This is due to the high factory readiness and complex digital technologies for the manufacture of modern wooden structures elements.  During the design, an information model was formulated in the SAPFIR software package with the subsequent possibility of importing the model  into  the  LIRA-SAPR  software  package.  Additional  steps  were  used  to  build  the  model: creating a 2D template in AutoCad with reference lines and the location of rigid walls on which the coating rests, and importing drawings into SAPFIR as a dxf-underlay; for all elements of the system located in the local coordinate system, auxiliary lines were built for the correct orientation of the plane in space; loads on curved surfaces were calculated in the PC Expri. For the further development of the nodes, 3D modeling was used with the transfer of the information model to the Tekla Structures PC as a specialized environment for the constructive section of the project. The presented calculation of a complex dome structure using wooden arches summarizes the approaches to the development of unique forms of structures using wood. The use of information models made it possible to reduce the time spent on design, to optimize the drawings, and also to significantly increase the complexity of the architectural and structural design of the structure and the design model, taking into account the nonlinear effects of wood.